Analysis of functional profile and mobility in Parkinson’s disease: a cross sectional study - Gomes, Wildja de Lima; Miranda, Larissa Melo de Souza; Silva, Neildja Maria da; Davi, Gisele Kariny Souza; Costa, Robison Carlos Silva; Regalado, Isabelly Cristina; Cacho, Roberta de Oliveira; Cacho, Enio Walker Azevedo; Lima, Núbia Maria Freire Vieira (Manual Therapy, Posturology & Rehabilitation Journal, 2018)
Background: Idiopathic Parkinson’s disease (PD) is a progressive neurodegenerative disease that has a prevalence of 18–328 per 100,000 in habitants in developing countries, with an estimated 3.3% of the Brazilian elderly population affected by PD throughout life. The classic symptoms include a resting tremor, muscular rigidity, bradykinesia and postural instability, which are all motor symptoms. The mobility of the subjects is compromised early, thus impairing their balance and limiting their ability to perform simple tasks. The restricted movement prevents dissociation between the head and trunk during walking, and freezing occurs as advanced disease reduces the progression of movements during walking. Objective: To analyze mobility and functionality profiles in subjects with Parkinson’s disease and compare them with healthy subjects. Method: A sample was consisted of 10 subjects with PD and 10 healthy elderly subjects. Assessment tools were used to quantify the severity of PD the scale Hoehn and Yah (HY), for mobility were used the Dynamic Parkinson’s Gait Scale (DYPAGS) and Modified Parkinson Activity Scale (PAS modified), for functionality were used the Unified Parkinson’s Disease Rating Scale (UPDRS) and dual task (DT) performance. Results: The subjects with PD showed worse performance in mobility and DT as determined by the modified PAS (p=0.0001) and DYPAGS (p=0.0001). Correlations were found between the UPDRS, the Gait Freezing Questionnaire (FOG), the PAS modified score, left-hand grip strength and the HY values (p<0.05). There were no differences in prehensile muscle strength between PD and healthy subjects. Conclusions: Subjects with PD showed decreased mobility and functionality for activities related to ADLs, gait and DT compared to healthy elderly subjects. Disease severity, muscle strength and freezing were correlated with the mobility and DT performance in subjects with PD.